2014
DOI: 10.1007/s00441-014-2001-y
|View full text |Cite
|
Sign up to set email alerts
|

Double-negative feedback loop between ZEB2 and miR-145 regulates epithelial-mesenchymal transition and stem cell properties in prostate cancer cells

Abstract: The invasion and metastasis of tumors are triggered by an epithelial to mesenchymal transition (EMT), which is regulated by microRNAs (miRNAs). EMT also promotes malignant tumor progression and the maintenance of the stem cell property, which endows cancer cells with the capabilities of self-renewal and immortalized proliferation. The transcriptional repressor zinc-finger E-box binding homeobox 2 (ZEB2), as an EMT activator, might be an important promoter of metastasis in some tumors. Here, we report that ZEB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 74 publications
8
119
0
Order By: Relevance
“…MiR-145 is a regulator of EMT during cancer progression. MiR-145 is often down-regulated in cancer tissues and restoration of miR-145 suppressed cancer cell invasion by reversing the EMT phenotype [12,28]. MiR-145 acts as a tumor suppressor in bladder cancer [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-145 is a regulator of EMT during cancer progression. MiR-145 is often down-regulated in cancer tissues and restoration of miR-145 suppressed cancer cell invasion by reversing the EMT phenotype [12,28]. MiR-145 acts as a tumor suppressor in bladder cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Since miR-145 was involved in EMT process in cancer cells [12], we asked whether the effect of TUG1 on cell invasion was mediated by miR-145. Fig.…”
Section: Mir-145/zeb2 Axis Mediated the Effect Of Tug1 On Emt In Bladmentioning
confidence: 99%
“…markers, such as vimentin, and up-regulating epithelial markers, such as E-cadherin, by directly targeting ZEB1 and ZEB2, which is a direct target of miR-145, too [57,58] (Figure 3). Ren et al [59] reported that ZEB2 also represses the transcription of miR-145, creating a double-negative feedback loop between ZEB2 and miR-145, which is a key in the control of EMT and stem cell properties during the bone metastasis of PCa. Besides, upregulation of miR-21 in PCa also plays an important role in EMT (Figure 3) by decreasing the BTG2 levels, initiating thus the acquisition of luminal markers and EMT [60,61].…”
Section: Role Of Mirnas In Prostate Cancermentioning
confidence: 99%
“…Among them we found foxo1a, also predicted to be a target in zebrafish. Another gene was zeb2, which has recently been shown to be a direct target of miR-145 (Ren et al, 2014). Within the ZEB gene family in zebrafish, zeb1a has a predicted miR-145 target site.…”
Section: Foxo1a Is Required For Lpm and Ismc Differentiationmentioning
confidence: 99%